Odpowiedzi

Najlepsza Odpowiedź!
2010-01-18T19:43:00+01:00
A) 3x+y=5
2x-y=0

5x=5 /;5
x=1

3x+y=5
x=1

3*1+y=5
x=1

3+y=5
x=1

y=5-3
x=1

y=2
x=1

b) 2x-y=5
x+y=4

3x=9 /:3
x=3

x+y=4
x=3

3+y=4
x=3

y=4-3
x=3

y=1
x=3

c) -x-y= -6
-x+y=2

-2x=-4 /:(-2)
x=2

-x+y=2
x=2

-2+y=2
x=2

y=2+2
x=2

y=4
x=2

d) 4x-5y= -4
-2x+3y=1,1 I * 2

4x-5y=-4
-4x+6y=2,2

y=-1,8

4x-5y=-4
y=-1,8

4x-5*(-1,8)=-4
y=-1,8

4x+9=-4
y=-1,8

4x=-4-9
y=-1,8

4x=-13 /:4
y=-1,8

x=-3,25
y=-1,8

e) -2x+y=0 I * 3
3x-3y=1

-6x+3y=0
3x-3y=1

-3x=1 /:(-3)
x=-1/3

3x-3y=1
x=-1/3

3*(-1/3)-3y=1
x=-1/3

-1-3y=1
x=-1/3

-3y=1+1
x=-1/3

-3y=2 /(-3)
x=-1/3

y=-2/3
x=-1/3


f) 3x-2y= -12
2x-5y= -19 I*(-1,5)

3x-2y=-12
-3x+7,5y=28,5

5,5y=16,5 /5,5
y=3

3x-2y=-12
y=3

3x-2*3=-12
y=3

3x-6=-12
y=3

3x=-12+6
y=3

3x=-6 /3
y=3

x=-2
y=3



2010-01-18T19:44:04+01:00
A) 3x+y=5
2x-y=0
5x=5
x=1
y=2

b) 2x-y=5
x+y=4
3x=9
x=3
y=1


c) -x-y= -6
-x+y=2
0=-4 - układ sprzeczny


d) 4x-5y= -4
-2x+3y=1,1
4x-5y=-4
-4x+6y=2,2
y=-1,8
4x + 9 = -4
4x= -13
x=3,25



e) -2x+y=0
3x-3y=1
-6x+3y=0
3x-3y=1
-3x=1
x=-1
y=-2


f) 3x-2y= -12
2x-5y= -19
-6x+4y=24
6x-10y=-38
6y=-14
y= -2 i jedna trzecia
x=16 i dwie szóste







2010-01-18T19:47:26+01:00
A)3x+y=5
2x-y=0
5x=5/:5
x=1
3x+y=5
3*1+y=5
y=5-3
y=2
b)2x-y=5
x+y=4
3x=9/:3
x=3
2*3-y=5
6-y=5
-y=-1/*-1
y=1